Cyclophosphamide inhibits Pax5 methylation to regulate the growth of retinoblastoma via the Notch1 pathway. (December 2021) - Jin, Lan; Ma, Xiaojie; Lei, Xiaoqin; Tong, Jing'an; Wang, Runsheng
Retinoblastoma (Rb) is the most common intraocular malignant tumor in infants. Here, we investigated the function and mechanism of cyclophosphamide (CTX) in the development of Rb. Real-time quantitative polymerase chain reaction (RT-qPCR) results showed that paired box protein 5 (Pax5) expression was down-regulated in Rb tissues and cell lines. Methylation-specific PCR (MSP) results showed that the methylation level of Pax5 was up-regulated in Rb. After treatment with CTX, the Pax5 expression in Rb cell lines was increased significantly. The methylation of Pax5 and the expression of DNA methyltransferases (DNMTs) were down-regulated in the CTX group. Cyclophosphamide inhibited cell proliferation, migration, and invasion, promoted cell apoptosis via the Notch1 pathway. DNA methyltransferase inhibitor SGI-1027 had synergistic effects with CTX. Paired box protein 5 siRNA was transfected into Y79 cells treated with CTX. The expression of DNMTs, Pax5, the Notch1 pathway and apoptosis marker protein was detected by Western blotting, and changes in cell behavior were detected, respectively. Results showed that knockdown of Pax5 reversed the effects of CTX. Moreover, the Notch1 activator Valproic acid (VPA) abolished the inhibitory effects of CTX on Rb development. Moreover, CTX inhibited tumor growth in nude mice. These findings demonstrated that CTX up-regulated Pax5 expression by down-regulating DNMTs expression, and then inhibited the Notch1 signaling pathway activation and Rb growth.